2008
DOI: 10.1089/jwh.2007.0584
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Opinions of Hormone Therapy Prior to the Women's Health Initiative: A Multinational Survey on Four Continents

Abstract: Women in all parts of the world suffer from symptoms associated with menopause, and many desire treatment. This study was conducted prior to the publication of the initial WHI and Million Women Study results, thereby providing a benchmark of patient attitudes about menopausal symptoms and the acceptability of different types and delivery modes of HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…The low rate of HRT use found in our study (2.1%) is comparable to those of other Asian countries [14,23]. Apart from cultural differences, the reasons were considered to be the lower prevalence and less severity of menopausal symptoms in the Asian population [23,31].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The low rate of HRT use found in our study (2.1%) is comparable to those of other Asian countries [14,23]. Apart from cultural differences, the reasons were considered to be the lower prevalence and less severity of menopausal symptoms in the Asian population [23,31].…”
Section: Discussionsupporting
confidence: 63%
“…After their publication, the use of HRT has decreased, in spite of new analyses of the WHI data. Recent follow-up and re-analysis of these data have found that in women aged 50-59 years, conjugated equine estrogens alone during the intervention phase were more favorable than placebo in all-cause mortality, myocardial infarction, deaths due to cancer and with regard to the global index [12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Women have menopauseassociated symptoms worldwide (1). Hormone replacement therapy (HRT) is a well-established form of treatment for such symptoms.…”
mentioning
confidence: 99%
“…Hormone replacement therapy (HRT) is a well-established form of treatment for such symptoms. However, patients and practitioners have undergone a significant change of thought regarding the use of HRT after the publication of two studies focusing on the risks of HRT, the Women's Health Initiative randomized controlled trial in 2002 and the observational Million Women Study in 2003 (1,2). Hormone replacement therapy also has been associated with an increased risk of breast cancer (3).…”
mentioning
confidence: 99%
“…While we do not have information on hormone replacement therapy for our respondents, evidence suggests that few Indonesian women have ever used hormone therapy for their menopausal symptoms [41].…”
Section: (B) Analysismentioning
confidence: 99%